Development of a LC-MS/MS method for the quantification of goniodomins A and B and its application to Alexandrium pseudogonyaulax strains and plankton field samples of Danish coastal waters. (1st December 2018) - Krock, Bernd; Tillmann, Urban; Wen, Yingying; Hansen, Per Juel; Larsen, Thomas Ostenfeld; Andersen, Aaron J.C.
Abstract: An external standard of goniodomin A (GDA) was prepared from a strain of Alexandrium pseudogonyaulax originating from New Zealand and its chemical structure was confirmed by nuclear magnetic resonance (NMR) spectroscopy. Using the GDA standard, an ultra-performance liquid chromatography-tandem mass spectrometric (UPLC-MS/MS) method in selected reaction monitoring (SRM) mode was developed for separation and quantification of GDA. This method was successfully applied to planktonic field samples collected during an oceanographic expedition conducted with R/V Uthörn along the Danish west coast, Limfjord and Kattegat in June 2016. In addition, this method was used to characterize goniodomin (GD) profiles of 17 A. pseudogonyaulax strains from the coastal North Sea and from Limfjord. Highest GDA levels were found in Limfjord (up to 590 ng NT −1 m −1 ), but GDA was also detected in the North Sea appearing at the latitude of Sylt Island northwards and in Kattegat from the eastern mouth of Limfjord down to the Kiel Bight, but at lower abundances than within Limfjord. This is the first reported detection of GDA in planktonic field samples. Chemical analysis of 17 strains of A. pseudogonyaulax revealed that all strains were producers of GDA (5–35 pg cell −1 ) as well as in most cases minor amounts (0.01–0.07 pg cell −1, expressed as GDA equivalents) of goniodomin B (GDB). Highlights: Presentation of an tandem mass spectrometry (LC-MS/MS) fort he quantification of goniodomins A and B. Survey of goniodomin A levels in the North Sea. Determination goniodomin profiles of 17 strains of Alexandrium pseudogonyaulax isolated from North Sea field populations.